Shopping pattern and food purchase differences among Supplemental Nutrition Assistance Program (SNAP) households and Non-supplemental Nutrition Assistance Program households in the United States - Gustafson, Alison (Prev Med Rep, 2017)
• SNAP households are influenced by proximity to stores in predicting store choice. • Store choice among SNAP households predicted beverage purchases. • SNAP households are more likely to purchase sugar-sweetened beverages at supercenters and convenience stores.